(untitled) (Journal of the College of Basic Education, 2022)
The study includes research in the specificity of opposites in modern Arabic poetry, especially the duality of silence and sound, which constituted a poetic style and feature that carried with it a philosophical and poetic stance, embodying a paradox on the expressive and semantic level if their texts were taken from what is familiar to interrogate reality and insert it into a more suggestive poetic reality, as if the poets sought Through this duality, to form a prominent and influential image that has an aesthetic and interpretive dimension to form more profound and influential scenes. That is, it came to express their suffering and their psychological distress